A finite element approach for the planning and simulation of 3D mandibular osteotomy for orthognathic surgery / Unaizah Hanum Obaidellah - Unaizah Hanum, Obaidellah (2006)
Facial deformities caused by accidents or malformation at birth highly influence the appearance and functionality aspects of an individual. Self-confidence and interpersonal relationships in addition to the ability of breathing, biting and speaking are the few factors affected by facial disharmony. Often corrective surgery known as orthognathic surgery is performed to resolve this issue. Careful and precise surgery planning is mandatory to ensure the success of a surgery that leads to a change in the facial morphology of an individual. The current technique used by craniofacial surgeons for predicting a patient’s post operative facial appearance is done by sketches on 2D lateral x-ray images resulting to less-accurate and unrealistic picture, thus leading to the need of a more realistic computerized 3D picture. Therefore, this dissertation presents a prototype system for the surgery planning involving bone cutting and repositioning particular to the human mandible as well as the prediction of the facial changes through simulation of the virtual orthognathic surgery. Actual preoperative patient data of Asian ethnicity is used and a computerized facial model is derived under the guidance of image processing methods in Mimics. The finite element method (FEM) available in MSC.AFEA is employed to accommodate numerical solution for mathematical formulations used for representing material properties of biological tissues. In addition, the contact analysis of FEM predicts the facial changes due to the underlying mandibular repositioning through dependant association in between the bone and the tissue. Results of the simulated facial appearance are presented using Amira and compared with the actual postoperative photograph.